Stalin’s Repressions and Rehabilitation of the Victims in the Politics of Memory in Uzbekistan - Malikov, Azim (Genocidas ir rezistencija, 2024)
This article is devoted to the analysis of how Stalin’s repressions are represented in the politics of memory in Uzbekistan, becoming part of the process of constructing a national ideological discourse. Uzbekistan’s multi-ethnicity and authoritarian system of governance have had a significant impact on understanding the country’s past and the formation of official memory. The research sources included official data, published memoirs, as well as individual interviews with witnesses of the era. The idea that Soviet repressions should be seen in the context of the anti-colonialist struggle against the aggression of the Russian Empire was not an invention of Uzbek political elites, but was developed by Uzbek cultural elites. The first president of Uzbekistan, Islam Karimov, in close dialogue with the Uzbek intellectual elite, contributed to the formation of a national memory of Soviet repressions and their victims. During this period, the rehabilitation of victims of Soviet repressions was carried out selectively. Since Shavkat Mirziyoyev came to power, there has been a more liberal government policy and a wider discussion of the issue of Soviet repressions and the rehabilitation of their victims. In official narratives, all residents of the former Uzbek SSR who suffered from Stalinist repressions, regardless of their political position, are considered victims of the Soviet regime. Unlike neighbouring countries, the political and cultural elite of Uzbekistan does not follow the ethnic principle of studying the victims of Soviet repressions, but adheres to internationalism and territoriality.